“To See Together Without Claiming to Be Another”: Stories as Relations, Against One-Direction Mode of Indigenous Stories Travelling - Kim, Eun-Ji Amy; Leclaire, Sandra-Lynn (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
Once communities’ stories are taken up by researchers and shared within the ivory tower of academia, the stories circulate within the ivory tower. It is often the case that these archived stories from communities are used by researchers, without asking permission from the communities where the stories originate. In this article, we aim to critically review and reflect on underlying theories and practices in conventional Eurocentric academia that allows for a ‘one direction’ mode of storytelling dissemination, allowing researchers to take the ‘version’ of community knowledge and/or stories without seeking the original approval from the communities themselves. We suggest ‘thoughtful’ questions for both settler and Indigenous researchers to consider in hopes of promoting ‘travelling back to original sources’ in their scholarly work.